2‐mm‐gate‐periphery GaN high electron mobility transistors on SiC and Si substrates: A comparative analysis from a small‐signal standpoint. Issue 6 (30th March 2021) - Jarndal, Anwar; Alim, Mohammad Abdul; Raffo, Antonio; Crupi, Giovanni
Abstract: In this paper, a comparative analysis has been conducted on GaN high electron mobility transistor (HEMT) technology on Si and SiC substrates. Small‐signal characteristics of 2‐mm GaN‐on‐Si and GaN‐on‐SiC devices have been investigated. Both devices have the same gate length of 0.5 μm. Special emphasis has been put on the temperature dependence of the buffer/substrate loading effects arising from the Si substrate. As a matter of fact, the "cold" pinch‐off admittance ( Y ‐) parameter measurement showed significant loading effect for the Si‐based device with respect to the SiC‐based one. This has been clearly supported by the analysis of the extracted parameters of the small‐signal equivalent‐circuit model. The model was also validated by simulating active scattering ( S ‐) parameters, which showed a very good agreement with the corresponding measurements. The results of this paper highlight the impact of buffer/substrate leakage currents on small‐signal characteristics and the importance of taking this into account during the modeling phase of the GaN‐on‐Si HEMT technology. The lower thermal conductivity of this substrate increases the internal temperature, thus stimulating more leakage and reduction of the device power efficiency.